A cylinder-shaped macrocycle formed via Friedel–Crafts reaction. Issue 36 (7th April 2021) - Zhu, Dingsheng; Fang, Shuai; Tong, Lu; Lei, Ye; Wu, Guangcheng; Chudhary, Tayba; Li, Hao
Abstract : By condensation of 1, 3, 5-tri(furan-2-yl) benzene and acetone, a macrocyclic host was synthesized via Friedel–Crafts reaction in a one-pot manner in 36% yield. Abstract : By performing Friedel–Crafts reaction with a mixture of 1, 3, 5-tri(furan-2-yl) benzene (TFB) and acetone, we successfully synthesized a cylinder-shaped macrocycle. The isolated yield of 36% is relatively high, considering that twelve C–C bonds are formed simultaneously. The structure of this macrocycle was confirmed using 1 H NMR spectroscopy, mass spectrometry and X-ray crystallography. This macrocycle is able to recognize a variety of cationic guests driven by cation–dipole and CH–π interactions.